From Knowing to Becoming: A Metacognitive–Spiritual Pedagogy for Transformative Islamic Education in Secondary Schools - Muhammad Hajirin Nur; Zurqoni; Abdul Majid; Taufikin Taufikin; Moses Adeleke Adeoye (GHAITSA : Islamic Education Journal, 2026)
This study arises from a paradox in Islamic Religious Education (IRE): although teaching often relies on textual and rule-based methods, these have not developed students' ability to reflect or transform their values. The study aims to develop and test the Pendidikan Agama Islam Based on Metacognitive Thinking Skills (PAI-BMTS) learning model, which integrates thinking, self-awareness, and spiritual aspects into a single teaching approach. The research uses Educational Design Research (EDR), which includes stages like investigation, design, creating materials, testing, and applying them in four Indonesian secondary schools with about 300 students and 5 teachers. The results show that the PAI-BMTS model has strong validity (Aiken’s V = 0.75–0.91), good reliability (Cronbach’s Alpha = 0.922), and works well in classrooms. Evidence shows that this model increases students' self-awareness, learning techniques, and adoption of Islamic values. Qualitative results also show that teaching has shifted from memorizing to thinking and reflecting, encouraging self-examination (muhasabah) for personal growth. The main contribution of this study is the creation of Metacognitive Spiritual Pedagogy, a method that combines reflective thinking with spiritual aspects in a complete learning cycle (the metacognitive–spiritual loop). This model expands how metacognition is understood and encourages a shift in Islamic education toward more reflection and transformation. The PAI-BMTS model supports both knowledge and complete personal growth.